Yahweh and the gods of Canaan a historical analysis of two contrasting faiths - Albright, William Foxwell, 1891-1971; Jordan, Louis H.; Jordan Lectures in Comparative Religion, School of Oriental and African Studies, University of London, 1965. (London Athlone, 1968)
Includes bibliographical references and indexes.
Keywords: Israel -- religion; Canaan -- religion